2015
DOI: 10.1021/acsami.5b01047
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Photocatalytic Assessment of Reactively Sputtered TiO2 Films

Abstract: Thin TiO2 films were prepared by DC magnetron reactive sputtering at different oxygen partial pressures. Depending on the oxygen partial pressure during sputtering, a transition from metallic Ti to TiO2 was identified by spectroscopic ellipsometry. The crystalline nature of the film developed during a subsequent annealing step, resulting in thin anatase TiO2 layers, displaying photocatalytic activity. The intrinsic photocatalytic activity of the catalysts was evaluated for the degradation of methylene blue (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
0
22
0
2
Order By: Relevance
“…The photocatalytic efficiency of the surfaces was evaluated from the decay in the absorbance peak using the slope of line ln(A 0 /A) vs. time. Table 4 presents the rate constant, k a , and the surface-normalised rate constant, k" [31]. Rafieian et al [31] collated k" values for MB degradation in the presence of TiO 2 prepared using various sputtering methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photocatalytic efficiency of the surfaces was evaluated from the decay in the absorbance peak using the slope of line ln(A 0 /A) vs. time. Table 4 presents the rate constant, k a , and the surface-normalised rate constant, k" [31]. Rafieian et al [31] collated k" values for MB degradation in the presence of TiO 2 prepared using various sputtering methods.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 presents the rate constant, k a , and the surface-normalised rate constant, k" [31]. Rafieian et al [31] collated k" values for MB degradation in the presence of TiO 2 prepared using various sputtering methods. The reported k" values range between 7.99 × 10 −8 and 2.87 × 10 −6 m s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Matsushita et al have developed photocatalytic microreactors with an immobilized TiO 2 layer [74]. The thermal oxidation [75], physical vapor deposition (PVD) [76], chemical vapor deposition (CVD) [77,78], dip-coating [79], spin-coating [80], electrospun [81], sputtering [82], sol-gel [83], and electrodeposit [84] methods are techniques for the film formation step needed in the design of immobilized photoreactors. Figure 9 represents a sol-gel-based deposition of TiO 2 inside a glass microtube.…”
Section: Immobilization Of Nanoparticles Inside the Microtubementioning
confidence: 99%
“…25,41 Kinetic studies can also be found for microreactors with immobilized photocatalyst. 24,42,43 For microreactors, although external mass transport limitations are often considered (see, e.g., ref. 44), internal (pore) diffusion limitations are not always discussed.…”
Section: Introductionmentioning
confidence: 99%